Challenges faced by basic school teachers in implementing learner-centred pedagogies in Hohoe, Ghana - Christopher Yao Dewodo; Prem Jotham Heeralal; Ambrose Agbetorwoka (Perspectives in Education)
This study examined basic school teachers’ challenges in Hohoe, Ghana, when implementing learner-centred pedagogies. It investigated three pedagogical approaches: constructivism, collaborative, and inquiry-based. The study employed a concurrent triangulation research design. It involved 392 respondents, comprising 364 teachers and 28 headteachers. A census method was used to engage all 364 teachers, while a purposive sampling technique was employed to select the 28 headteachers. Data were gathered through questionnaires for the quantitative phase and focus group discussions for the qualitative phase. Quantitative data were analysed using mean and standard deviation, while qualitative data were subjected to content-thematic analysis. The findings revealed that basic school teachers in Hohoe encountered several challenges when using learner-centred pedagogical approaches. Specifically, the constructivist approach was difficult to implement due to resource constraints. The collaborative approach faced issues related to students’ unwillingness to work in groups and difficulties in teacher assessment. The inquiry-based approach was hindered by teacher unfamiliarity and lack of necessary resources.